Constraint - Induced Movement Therapy: Determinants and Correlates of Duration of Adherence to Restraint use Among Stroke Survivors with Hemiparesis - Arinola Olasumbo Sanya; Olumide Olasunkanmi Dada (Disability, CBR and Inclusive Development)
Background: Constraint-Induced Movement Therapy (CIMT) was developed to improve purposeful movement of the stroke-affected extremity by restrictingthe use of the unaffected extremity. The two main components of CIMT are the training of the more-impaired arm to perform functional tasks, and the restraint of the less-impaired arm. One challenge that the application of CIMT faces is in ensuring adherence to the use of restraint. Purpose: There is a need to determine the factors that may influence adherence, as this would allow CIMT to be delivered more effectively, and prevent situations where unrealistic expectations are placed on stroke–affected individuals. Methods: Thirty stroke survivors with hemiparesis who met the inclusion criteria were consecutively recruited from the physiotherapy out-patient clinics, using a purposive sampling technique. A structured questionnaire was used to obtain information on clinical and socio-demographic parameters. The participants were given a restraint and an adherence time log-book, to make a daily record during the period they wore the restraint. The adherence time logbook was collected at the end of every week of the 3-week study. Motor function and functional use of the upper limb were measured using Motricity Index and Motor Activity Log respectively. Data was analysed using mean and standard deviations, independent t-test and Spearman rho; p was significant at 0.05. Results: Gender (p=0.73) and side affected/handedness (p=0.79) had no significant influence on the percentage duration of adherence to restraint use (DARU). The influence of socio-economic status was seen, with the participants of middle socio-economic status adhering for longer duration (p=0.02). Age had weak and no significant correlation with percentage DARU (p=0.55). There was significantly fair correlation between motor function/functional use at any stage (p=0.55) and the corresponding percentage duration of adherence to restraint use, except the functional use in the first week (p=0.44). Conclusion: Socio-economic status should be considered when applying CIMT. DOI: 10.5463/dcid.v22i3.84